KARAKTERISTIK PERTUMBUHAN EKONOMI DAN SEKTOR BASIS PROVINSI DI INDONESIA PADA MASA PANDEMI COVID-19 - Mohammad Ammar Alwandi; Siti Muchlisoh (Seminar Nasional Official Statistics, 2020)
The Covid-19 pandemic caused Indonesia’s economy to contract by 5.32 percent. Almost all business fields came under pressure in the second quarter of 2020. This is due to the massive transmission of Covid-19 in factories and offices. In addition, the implementation of large-scale social restriction (PSBBs) has decreased household consumption. The impact of a pandemic in each province is certainly different from one another, so that the policies cannot be generalized. Therefore, this study aims to analyze the characteristics of economic growth and base sector in provinces in Indonesia during the Covid-19 pandemic. This study uses the Location Quotient method to identify base sector in each province and K-Means Clustering method to map the characteristics of each province. The result of this study are provinces with an agricultural base sector and have low risk of Covid-19 transmissions which is relatively have low economic contraction. Thus, the government must continue to prioritize preventing the spread of Covid-19 while at the same time restoring the economy from agricultural sector.